Selling of the president 1968 - McGinniss, Joe (London, 1969)
What makes you cast your ballot? A Presidential candidate or a good campaign? How he stands on the issues or how he stands up to the camera? The Selling of the President is the enduring story of the 1968 campaign that wrote the script for modern Presidential politicking$1 (Band how that script came to be. It introduces: Harry Treleaven, the first adman to suggest that issues bore voters, that image is what counts. Roger Ailes, a PR man who coordinated the TV presentations that delivered the product. Frank Shakespeare, the man behind the whole campaign, who, after eighteen years at CBS, cast the image that sold America a President. And the candidate, Richard Nixon himself$1 (Ba politician running on television for the highest office in the land.s
Keywords: Political Science